1995
DOI: 10.1111/j.1939-1676.1995.tb01077.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cyclosporine Versus Standard Care in Dogs With Naturally Occurring Glomerulonephritis

Abstract: Glomerulonephritis (GN) is a leading cause of chronic renal failure in dogs. However, little is known about the efficacy of available treatment options for GN in this species. The purpose of this study was to determine the effects of cyclosporine (Cy) administration on the outcome of naturally occurring GN in dogs. Thirteen dogs from 4 institutions were included in the study. Randomization of dogs into placebo-versus Cy-treated groups was stratified according to initial morphological diagnosis and contributing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 27 publications
(4 reference statements)
1
15
0
Order By: Relevance
“…Although cyclosporine A itself can also result in interstitial fibrosis, we noticed no effect of cyclosporine A on the interstitial area in either normal dogs or affected male dogs. This may be a reflection of the drug levels maintained in this study; these values have been shown to be safe for use in dogs (26). Similarly, the patients with Alport syndrome who received cyclosporine A were reported to show no evidence of toxicity on biopsy (21), although no morphometry was done.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Although cyclosporine A itself can also result in interstitial fibrosis, we noticed no effect of cyclosporine A on the interstitial area in either normal dogs or affected male dogs. This may be a reflection of the drug levels maintained in this study; these values have been shown to be safe for use in dogs (26). Similarly, the patients with Alport syndrome who received cyclosporine A were reported to show no evidence of toxicity on biopsy (21), although no morphometry was done.…”
Section: Discussionmentioning
confidence: 77%
“…This dose was adjusted to maintain trough concentrations (16 h after the last dose) between 100 and 400 ng/ml. By 6 mo of age, the desired trough concentrations were attained at the recommended daily dose rate of approximately 10 mg/kg (26). Cyclosporine A was administered throughout the duration of the study.…”
Section: Subjectsmentioning
confidence: 99%
“…Uncommonly, cyclosporine may cause idiosyncratic hepatotoxicity, which does not seem to be dose‐dependent; gingival hyperplasia and hypertrichosis also have been reported occasionally . Nephrotoxicity is a potential problem in people receiving cyclosporine, but clinically relevant renal damage has not been documented in dogs at standard dosages …”
Section: Results and Recommendationsmentioning
confidence: 99%
“…The cyclosporine‐cyclophilin complex inhibits calcineurin, which is essential for the transcription of interleukin 2 and interleukin 2 activation of T lymphocytes . The effectiveness of cyclosporine in dogs with spontaneous glomerular disease has been evaluated in a randomized, controlled clinical trial, but was found to provide little apparent benefit . A limitation of this study was the lack of precise pathologic characterization of the tested glomerular diseases for evidence of active immune‐mediated injury potentially responsive to cyclosporine.…”
Section: Drug Options For Immunosuppressive Therapy Of Glomerular Dismentioning
confidence: 99%